Exploring the antecedents of collaborative learning performance over social networking sites in a ubiquitous learning context. (February 2015) - Liao, Yi-Wen; Huang, Yueh-Min; Chen, Hsin-Chin; Huang, Shu-Hsien
Highlights: The behavioral models associated with social network sites in a U-learning context. We examine the influential factors in students' learning of social network sites. The richness of social network sites produces positive usage attitudes of students. Abstract: Recent mobile and Internet applications have made possible the development of ubiquitous learning (U-learning). One such application is social networks, which allow people to create and exchange information with each other in a collaborative manner, and these are especially popular with so-called "digital natives, " who have grown up using such technologies. This study thus explores the behavioral models associated with using social network websites in a U-learning context. To carry out a more comprehensive investigation, a modified technology acceptance model (TAM) is developed, augmented with external factors, including collective efficacy and personal innovativeness in information technology (PIIT). This model is then used to examine the influential factors in students' use of social networks to learn, and also to evaluate their learning attitudes and usage effects. This study collected 321 valid questionnaires and used them to test the proposed model. The results show that personal innovativeness in information technology and collective efficacy affect learner attitudes through perceived playfulness, perceived usefulness, and perceived ease of use, and in turn affect dimensions, such as satisfaction, self-perceived usage effects, and continued usage intention. Based on these results, instructional designers should work to use the diversity and richness of existing social network sites to enhance learner perceptions of the playfulness and usefulness of information technology, which in turn can produce more positive usage attitudes and greater learning satisfaction.